2017
DOI: 10.1002/app.45574
|View full text |Cite
|
Sign up to set email alerts
|

Tough thiourethane thermoplastics for fused filament fabrication

Abstract: Fused filament fabrication (FFF) is the most common form of additive manufacturing. Most FFF materials are variants of commercially available engineering plastics. Their performance when printed can widely vary, thus there is an increasing volume of research on alternative materials with thermal and mechanical performance optimized for FFF. In this work, thiol-isocyanate polymerization is used for the development of a one-pot synthesis for polythiourethane thermoplastics for tough three-dimensional (3D) printi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Recently, Endo et al used the thiol–isothiocyanate reaction to synthesize aliphatic polydithiourethanes, which have an ability to be reprocessed because of the reversible C–S bond of the dithiocarbamate moiety. Nevertheless, the activation temperature of dithiourethane is 150 °C, which is higher than that of the reversible reaction of the urethane bond. , Besides, the thiol–isocyanate reaction has also been reported to produce polythiourethanes with good mechanical performance. , Indeed, it attracts our attention because the resulting polythiourethane has a structure very similar to that of polyurethane. We expect to develop a dynamic polyurethane network without significantly sacrificing the mechanical properties by incorporating this reversible interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Endo et al used the thiol–isothiocyanate reaction to synthesize aliphatic polydithiourethanes, which have an ability to be reprocessed because of the reversible C–S bond of the dithiocarbamate moiety. Nevertheless, the activation temperature of dithiourethane is 150 °C, which is higher than that of the reversible reaction of the urethane bond. , Besides, the thiol–isocyanate reaction has also been reported to produce polythiourethanes with good mechanical performance. , Indeed, it attracts our attention because the resulting polythiourethane has a structure very similar to that of polyurethane. We expect to develop a dynamic polyurethane network without significantly sacrificing the mechanical properties by incorporating this reversible interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers with divalent counterions provided beneficial melt rheological profiles for FDM due to stronger ionic interactions compared to monovalent counterparts. Printing of these polymers generated an array of complex geometries for controlled release applications. , Recently, Ellson et al reported the synthesis of thiourethane thermoplastics for FDM through step-growth polymerization of 2,20-(ethylenedioxy)­diethanethiol (EDDT) and hexamethylene diisocyanate (HDI) . The presence of thermally reversible hydrogen bonds facilitated processing at high temperatures and contributed to excellent mechanical toughness (up to 92 MJ/m 3 ) in molded or printed parts.…”
Section: Introductionmentioning
confidence: 99%
“…The respective load‐elongation curves of different fiber samples are shown in Figure . All samples display loading‐strain tensile curves with three stages typical for semicrystalline polymers: At the first stage, the force increases linearly with elongation until it reaches a yield point. Necking (stress‐induced, abrupt decrease in filament cross‐sectional area) appears at the subsequent stage, where the force remains almost constant.…”
Section: Resultsmentioning
confidence: 99%